2022
DOI: 10.1063/5.0092997
|View full text |Cite
|
Sign up to set email alerts
|

Efficient hydrogen evolution reaction at the phase transition boundary of polymorphic Mo1−xWxTe2

Abstract: Phase engineering of two-dimensional transition-metal dichalcogenides (TMDs) has been the subject of considerable interest as it represents a promising strategy for a highly active hydrogen evolution reaction (HER). However, various types of active sites on the basal planes and edges of TMDs have shown complicated mechanisms of the HER in TMDs, hindering the systematic engineering of the catalytic activity of TMDs. Here, we report the intrinsic basal-plane activity of a series of TMDs, Mo1−xWxTe2, whose phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Additionally, Suyeon et al. presented findings on a series of Mo 1– x W x Te 2 catalysts . They demonstrated that by adjusting the doping ratio ( x ), it is possible to induce phase transitions among the semiconductor 2H phase, metallic 1T phase, and a mixed 2H–1T phase.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Suyeon et al. presented findings on a series of Mo 1– x W x Te 2 catalysts . They demonstrated that by adjusting the doping ratio ( x ), it is possible to induce phase transitions among the semiconductor 2H phase, metallic 1T phase, and a mixed 2H–1T phase.…”
Section: Applicationsmentioning
confidence: 99%
“…Additionally, Suyeon et al presented findings on a series of Mo 1−x W x Te 2 catalysts. 177 They demonstrated that by adjusting the doping ratio (x), it is possible to induce phase transitions among the semiconductor 2H phase, metallic 1T phase, and a mixed 2H−1T phase. Notably, the HER catalytic activity of Mo 1−x W x Te 2 reaches its zenith at the boundary between the 2H and 1T phases when x = 0.09, achieving an impressive HER conversion rate of 0.692 s −1 (TOF value).…”
Section: Grain Boundarymentioning
confidence: 99%
“…of semiconducting 2H and metallic 1T′ phase of TMD alloy, Mo 1– x W x Te 2 for electrochemical reaction. Image (A) is reproduced from ref . Copyright 2022 AIP Publishing.…”
Section: Devices With Homo- and Heterophase Interfacesmentioning
confidence: 99%
“…Since 2D materials have many types of active sites according to the lattice arrangements, many efforts have been devoted to studying the catalytic activity of the defects, dislocations, dopant atoms, edge atoms, , and phase interfaces , as shown in Figure A. The nanoscale probe techniques such as scanning tunneling microscopy (STM) and transmittance electron microscopy (TEM) have facilitated to study of the physical and chemical properties.…”
Section: Devices With Homo- and Heterophase Interfacesmentioning
confidence: 99%
“…Thus, it is critical to develop a sensitive photodetector (PD) to monitor UVC radiation during daylight hours. [10][11][12] In recent years, wide bandgap semiconductors (E g > 4.43 eV), such as AlGaN, MgZnO, b-Ga 2 O 3 , GaN, NiO, BN, and LaAlO 3 , have been increasingly used to detect solar-blind UV. Studies related to UVC detectors and their respective performance are presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%